(untitled) (African Journal of Biomedical Research, 2023)
Intimate partner violence (IPV) is the most common form of domestic violence in Nigeria and a violation of human rights. Many women are unaware of their sexual and reproductive rights (SRRs) and are unable to exercise them especially in the face of violations to their persons by an intimate partner. There is paucity of information on women’s understanding of their SRRs and how it relates with their experience of IPV in Nigeria. The study was conducted to assess the knowledge, prevalence and pattern of IPV among female secondary school teachers and to determine the association between knowledge of SRRs and experience of IPV in Southwest Nigeria. A cross-sectional study was conducted among 364 teachers using a multi-stage sampling technique. A semi-structured self-administered questionnaire was used to obtain information on respondents’ knowledge of SRRs and experience of IPV. Data was analysed with SPSS version 20 and descriptive statistics were computed. Association between SRRs and experience of IPV was tested using Chi-square at p<0.05. One hundred and fifty (41.2%) of the respondents had good knowledge of SRRs. About 60% had ever experienced at least one form of IPV (sexual: 19.8%; verbal: 42.9%; physical: 8.0%; emotional: 38.2%). Significantly, higher proportion of respondents with good knowledge of SRRs experienced verbal IPV compared to 34% of those with poor knowledge (p =0.006). The study revealed poor knowledge of SRRs and high prevalence of IPV among the study population. Female teachers, as victims of IPV and custodians of knowledge, will benefit from on-the-job training regarding SRRs.